Acceptance and Compliance of Continuous Positive Airway Pressure in Patients with Obstructive Sleep Apnea: Local Population Survey - Mohammed A. Al-Abri; Ahmed Al-Harmeli; Mahmoud Al-Habsi; Deepali Jaju (Oman Medical Journal, 2020)
Objectives: Continuous positive airway pressure (CPAP) compliance of > 4 hours per night has been considered acceptable to achieve clinical improvements in patients with obstructive sleep apnea (OSA). However, the factors determining CPAP adherence are unclear. This study aims to address the issue of acceptance and adherence to CPAP treatment in the Omani population and to determine the factors affecting adherence to CPAP. Methods: This retrospective study included adult OSA patients who underwent polysomnography between January 2008 and December 2014 (n = 3046). Demographic information, Epworth Sleepiness Scale (ESS), apnea/hypopnea index (AHI), and desaturation events were collected from the sleep laboratory records. Subjects were grouped as CPAP users and CPAP non-users. CPAP users were divided into compliers (> 4 hours/night) and non-compliers (< 4 hours/night). Student’s t-test was used to find differences in CPAP users and non-users, compliers, and gender differences in CPAP users. The association of CPAP compliers and non-compliers with age, gender, AHI, ESS, and comorbidities were assessed using the chi-square test. Results: Out of the 90.0% patients advised CPAP treatment, 34.7% came for regular CPAP follow-up. Total CPAP compliers were 59.3% (n = 274). The CPAP users had higher age, high ESS, baseline AHI, and more oxygen desaturation events than CPAP non-users (p < 0.010). Among the CPAP users, females were significantly older than males and had more oxygen desaturation events. CPAP compliers had significantly higher baseline AHI and more oxygen desaturation events. There was no association between CPAP compliance and age, gender, AHI, ESS, or comorbidities. Conclusions: CPAP users and compilers have severe OSA. CPAP acceptance and adherence are suboptimal and could not be predicted by age, gender, AHI, ESS, or comorbidities.